A Review of Self-Expanding Esophageal Stents for the Palliation Therapy of Inoperable Esophageal Malignancies - Kang, Yunqing (Biomed Res Int, 2019)
Esophageal cancer is a very deadly disease, killing more than 15,000 people in the United States annually. Almost 400,000 new cases happen in the worldwide every year. More than 50% esophageal cancer patients are diagnosed at an advanced stage when they need an esophageal stent to open the blocked esophagus for feeding and drinking. Esophageal stents have evolved in stages over the years. Current clinically used stents commonly include stainless steel or nitinol self-expandable metallic stent (SEMS) and self-expandable plastic stent (SEPS). There are many choices of different types of stents and sizes, with fierce competition among manufacturers. However, current stent technology, whether uncovered, partially covered, fully covered SEMS or SEPS, has their own advantages to solve the dysphagia, stricture, and fistula problems, but they also cause some clinical complications. The ideal stent remains elusive. New 3D printing technique may bring new promising potential to manufacturing personalized esophageal stents. Drug-eluting stents could be the new avenue to do more than just pry open a stricture or cover a defect in the esophageal lumen, a possibility of proving local anticancer therapy simultaneously. Additionally, the lack of esophageal cancer animal models also hinders the progress of stent development. This paper reviews these topics for a comprehensive understanding of this field. In a conclusion, the ultimate goal of the future esophageal stent would have multifunction to treat the underlying conditions and restore esophageal function to near normal.